Risk at the margins - Pollock, William (2019)
Quantitative landslide risk analysis is a key step in creating appropriate land use policies. The forced migration of those displaced by recent armed conflict in Syria has highlighted the need for studies to guide humanitarian aid and resettlement policies. Over 1.5 million displaced Syrians now reside in Lebanon, self-settling throughout the country through urban integration and informal encampment due to Lebanon's prohibition of formal refugee camps. The Syrian-Lebanon refugee crisis coincides with the recent reexamination of the established aid practice of camp-based resettlement, focused on issues of aid efficacy, security, and human dignity but lacking an environmental hazards perspective. In light of these issues, we quantitatively assess the landslide risk profile of Lebanon, finding a 75% increase in landslide risk since the start of the Syrian crisis. The risk is highest in the debris flow-prone mountains of central and northeastern Lebanon. Additionally, Syrian refugees settled in informal camps experience 9–11 times greater risk then urban populations due to sub-standard shelter, suggesting that urban rather than camp-based resettlement policies are preferable from an environmental-hazards perspective.